2015
DOI: 10.1007/978-3-319-24858-5_8
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion Detection System for Applications Using Linux Containers

Abstract: Abstract. Linux containers are gaining increasing traction in both individual and industrial use, and as these containers get integrated into mission-critical systems, real-time detection of malicious cyber attacks becomes a critical operational requirement. This paper introduces a realtime host-based intrusion detection system that can be used to passively detect malfeasance against applications within Linux containers running in a standalone or in a cloud multi-tenancy environment. The demonstrated intrusion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The major advantage of this approach is that it provides a high degree of flexibility in the form of scenarios that can be adapted to individual technical as well as policy requirements. For example, the evaluation MySQL example 9 from chapter V can easily be adapted using real network data. With this approach we have created a new data set.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The major advantage of this approach is that it provides a high degree of flexibility in the form of scenarios that can be adapted to individual technical as well as policy requirements. For example, the evaluation MySQL example 9 from chapter V can easily be adapted using real network data. With this approach we have created a new data set.…”
Section: Discussionmentioning
confidence: 99%
“…It was published as "Leipzig Intrusion Detection -Data Set (LID-DS)" in [8] which contains different use cases shown in table II. LID-DS framework and ready to use data sets are free to use and published on GitHub 9 . It is the first HIDS data set which contains normal and abnormal behavior, system calls and their timestamps, thread ids, process names, 9 https://github.com/LID-DS/LID-DS arguments, return values and excerpts of their data buffers from traces of normal and attack behavior of several recent, multi-process, multi-threaded scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we propose a resilient intrusion detection system (RIDS) for misbehaving containers that extends upon the former work previously applied to standalone containers (Abed et al, 2015) to be used in cloud environments, where a colony of similar containers may collaborate to complete a certain task.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent survey, Modi et al (2013) concluded that cloud environments should incorporate intrusion detection and prevention systems to address one of the major concerns of cloud users after data security. To address those concerns, Abed et al (2015Abed et al ( , 2016 presented a simple host-based intrusion detection system (HIDS) that monitors system calls between the container processes and the host kernel for malfeasance detection.…”
Section: Introductionmentioning
confidence: 99%